2018
DOI: 10.1097/pcc.0000000000001625
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations on Selection and Processing of RBC Components for Pediatric Patients From the Pediatric Critical Care Transfusion and Anemia Expertise Initiative

Abstract: The Transfusion and Anemia Expertise Initiative consensus conference developed recommendations for selection and processing of RBC units for critically ill children. Recommendations in this area are largely based on pediatric and adult case report data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…The consensus recommendations of TAXI are presented below. All justifications, literature supporting the recommendations from the systematic review, as well as discussion of research priorities within the 9 subgroups are presented in separate subgroup manuscripts in a supplement of Pediatric Critical Care Medicine (3139). The subgroups developed, scored and finalized 100 recommendations (55 specific clinical recommendations, and 45 research recommendations, which are presented separately, by subgroup) and 2 good practice statements, of which all met a priori > 80% agreement.…”
Section: Resultsmentioning
confidence: 99%
“…The consensus recommendations of TAXI are presented below. All justifications, literature supporting the recommendations from the systematic review, as well as discussion of research priorities within the 9 subgroups are presented in separate subgroup manuscripts in a supplement of Pediatric Critical Care Medicine (3139). The subgroups developed, scored and finalized 100 recommendations (55 specific clinical recommendations, and 45 research recommendations, which are presented separately, by subgroup) and 2 good practice statements, of which all met a priori > 80% agreement.…”
Section: Resultsmentioning
confidence: 99%
“…Both neonatal and pediatric expert guidelines recommend irradiation of cellular blood products for those at risk for transfusion-associated graft versus host disease or those that may have undiagnosed immunodeficiencies that put them at risk for transfusion-associated graft versus host disease. 20,21 Though observational studies have suggested RBC storage duration may impact outcome, 22,23 clinical trials have not demonstrated a difference, including studies in children and neonates. [24][25][26] Controversy exists regarding the importance of ABO matching for platelet transfusions, especially regarding the practice in critically ill children.…”
Section: Discussionmentioning
confidence: 99%
“…Infants more commonly received irradiated RBCs and RBCs with a shorter storage duration than children. Both neonatal and pediatric expert guidelines recommend irradiation of cellular blood products for those at risk for transfusion‐associated graft versus host disease or those that may have undiagnosed immunodeficiencies that put them at risk for transfusion‐associated graft versus host disease 20,21 . Though observational studies have suggested RBC storage duration may impact outcome, 22,23 clinical trials have not demonstrated a difference, including studies in children and neonates 24–26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfusion in pediatrics and neonatology should be used in accordance with the recommendations for transfusion in pediatrics and neonatology. In the further development of these transfusion indications, it is necessary to report in more detail the adverse reactions to transfusion in neonatals and prematures [1,35,36,44].…”
Section: Discussionmentioning
confidence: 99%